PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN DALAM PERSPEKTIF ISLAM - P Pardomuan Siregar (Bisnis-Net, 2018)
Economic growth is one of the important conditions for human needs fulfillment. The absence ofgrowth means the stagnant activity of economic life that will result in less to say no loss of incomewhich is a basic human need. Economic growth can be seen from various indicators. These indicatorsinclude increased output (out put), the creation of new jobs, rising investment climate and so forth.Welfare is the goal of Islamic teachings in the economic field. Welfare is a part of rahmatan lilalamin taught by this Islamic religion. But the welfare that is meant in the Qur'an is not unconditionalto get it. Welfare will be given by Allah SWT if man does what he enjoins and keeps away from whathe forbids. The verses of the Qur'an that provide explanations about welfare are directly (explicitly)and some are indirectly (implicitly) related to economic problems. Nevertheless, this two-wayexplanation becomes a view of welfare.